República Federativa Evangélica: uma análise de gênero sobre a laicidade no Brasil a partir da atuação dos/as parlamentares evangélicos/as no Congresso Nacional no exercício da 54ª Legislatura - Costa, Emerson Roberto da (2016)
This research aims to analyze the relationship between religion and politics under the gender perspective considering the role of evangelical parliamentarians in the 54th Legislature (2011-2014) and how they intervene in the Brazilian political space as the enactment of laws and the development of public policies that comprehend, among others, the regulation of abortion, criminalization of homophobia, the stable union between people of the same sex and the challenges resulting from this position for the Brazilian State that has positioned itself as laic. But if laic refers to the idea of state neutrality in religious matters, legislate legitimized by certain principles based on religious doctrines may suggest the suppression of freedom and equality, the lack of diversity and plurality recognition and the absence of boundaries between public, collective and private or personal interests. The methodological procedures for development of this research are based on the analysis and interpretation of literature in order to establish the relationship between religion and politics, the conceptualization, qualification and classification of phenomenon of laicity; documentary survey; analysis of the speeches of evangelical parliamentarians published by media, delivered in the plenary session or adopted to support projects laws; qualitative research with interviews and observation of public postures adopted of parliamentary members of Frente Parlamentar Evangélica– FPE (Evangelical Parliamentary Front). In this sense, the postulates of Religious Studies, properly correlated with the interpretation of the data set obtained in the search field, may identify the place of the religious one in the society interactively with the laicity interfaces aiming to deepen the understanding regarding democracy, the role of religion in contemporary societies and the diffuse, collective and individual rights of people.